Early Recognition of Drug-Induced Febrile Neutropenia Leads to an Improved Outcome in the Trauma Intensive Care Unit: A Case Report - Bisman J.K. Khurana; Amarjyoti Hazarika; Kajal Jain (Journal of Neuroanaesthesiology and Critical Care)
Traumatic brain injury necessitates the use of antiepileptics for seizure prophylaxis, which are associated with multiple side effects including neutropenia, which may be dose dependent or idiosyncratic. We report the case of a young male with traumatic brain injury who developed febrile neutropenia, likely secondary to antiepileptic use. Early recognition and stopping of the drugs with use of granulocyte colony-stimulating factor led to the successful management of the patient.